Hubungan Pola Makan, Tingkat Stres Dan Perilaku Olahraga Dengan Penyakit Hipertensi Pada Karyawan Di PT. X Jakarta Selatan : Relationship Between Diet, Stress Levels and Exercise Behavior with Hypertension in Employees at PT. X South Jakarta - Astuti, Suci Willy (Dohara POAJ, 2025)
Introduction: Hypertension is a non-communicable disease but this disease is the cause of the most deaths in the world. Hypertension can be caused by several factors including diet, stress levels and exercise behavior. Methods: This study used a cross-sectional approach to determine the level of correlation produced with the study population, namely employees of PT. X South Jakarta. The sample in this study was 58 people. The instruments in this study were the FFQ, DASS and sports behavior questionnaires. Data collection is done by filling out a questionnaire. Data processing with the SPSS computer program uses the Chi-Square test. Results: The majority of respondents in this study were aged 51-55 years (29,30%); the majority were male (58,60%) and the majority had diploma education (41,40%). More than half experienced mild stress (67,20%); had a good diet (55,20%) and did not exercise regularly (74,10%). The results of the chi-square test analysis showed p-value of 0,002 and 0,000 on H1 and H2 so there is a relationship between diet and stress levels on hypertension. Different results showed that there was no relationship between exercise behavior and the incidence of hypertension with a p-value of 0,309 (p > 0,05). Discussion: There is a relationship between diet and stress levels with hypertension in PT. X employees in South Jakarta, but there is no relationship between exercise behavior and hypertension in PT. X employees in South Jakarta.